Biomaterials science : an introduction to materials in medicine - Wagner, William R.; Sakiyama-Elbert, Shelly E.; Zhang, Guigen; Yaszemski, Michael J. (Academic Press, an imprint of Elsevier, 2020)
This revised edition of Biomaterials Science is the most comprehensive single text on all aspects of biomaterials science from principles to applications. Fully revised and updated to address issues of translation, nanotechnology, additive manufacturing, organs on chip, precision medicine and more. Online chapter exercises are available for most chapters.